RENCANA USAHA MENDIRIKAN APARTEMEN DI AIRMADIDI - Soewignyo, Tonny (JBE (Journal of Business and Economics); Volume 6 No.2, 2007 JBE UNKLAB, 2007)
A safe and convenient place to stay for students of Universitas Klabat is really needed to attract more students to study and do their activities in the campus. This study aimed to survey the prospect of building an apartment with all facilities required by university students. A location close to Universitas Klabat, Airmadidi is available to build the apartment and is expected to have a good future earning to the investor who is interested in this investment.